Serving two masters : the development of American military chaplaincy, 1860-1920 - Budd, Richard M., 1951- (University of Nebraska Press, 2002)
"Military chaplains have a long and distinguished tradition in the United States, but historians have typically ignored their vital role in ministering to the needs of soldiers and sailors. Richard M. Budd corrects this omission with a history of the chaplains who sought to create a viable institutional structure for themselves within the U.S. Army and Navy that would best enable them to minister to the fighting men."--Jacket